2023
DOI: 10.1111/gcb.16553
|View full text |Cite
|
Sign up to set email alerts
|

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget

Abstract: Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration (Reco), net ecosystem CO2 exchange (NEE; Reco − GPP), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 165 publications
3
37
0
Order By: Relevance
“…(2020) applied a process‐based model to simulate North American peatland C storage over the last 12,000 years and found that these peatlands accumulated 85–174 Pg C over the study period, but that peat decomposition and permafrost degradation complicate future predictions of the sink strength (Jones et al., 2023). Two studies conducted at the pan‐Arctic scale indicate, based on CO 2 alone, the boreal region remains a net sink of CO 2 for the years 1990–2015 with much of this sink strength derived from the boreal uplands, particularly those in the Eurasian boreal region, and Siberia in particular (Virkkala et al., 2021; Watts et al., 2023). Considering only evergreen boreal forests, recent work finds a net sink of 0.4 Pg C year −1 between 1981–2018, but there is no trend toward increasing in CO 2 uptake as increases in GPP are compensated for by losses due to ER, with large interannual variability (Pulliainen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) applied a process‐based model to simulate North American peatland C storage over the last 12,000 years and found that these peatlands accumulated 85–174 Pg C over the study period, but that peat decomposition and permafrost degradation complicate future predictions of the sink strength (Jones et al., 2023). Two studies conducted at the pan‐Arctic scale indicate, based on CO 2 alone, the boreal region remains a net sink of CO 2 for the years 1990–2015 with much of this sink strength derived from the boreal uplands, particularly those in the Eurasian boreal region, and Siberia in particular (Virkkala et al., 2021; Watts et al., 2023). Considering only evergreen boreal forests, recent work finds a net sink of 0.4 Pg C year −1 between 1981–2018, but there is no trend toward increasing in CO 2 uptake as increases in GPP are compensated for by losses due to ER, with large interannual variability (Pulliainen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Zhuang et al (2020) applied a process-based model to simulate North American peatland C storage over the last 12,000 years and found that these peatlands accumulated 85-174 Pg C over the study period, but that peat decomposition and permafrost degradation complicate future predictions of the sink strength (Jones et al, 2023). Two and Siberia in particular (Virkkala et al, 2021;Watts et al, 2023).…”
Section: Source Versus Sink Strength Of C Across the Circum-boreal Re...mentioning
confidence: 99%
“…Furthermore, permafrost regions have a great potential to emit much more CH 4 (Treat et al., 2018; Zona et al., 2016). It was estimated that regional CH 4 emissions from tundra and boreal wetlands were approximately 35 Tg CH 4 ‐C year −1 using a satellite data‐driven process‐model for northern ecosystems (Watts et al., 2023). Similar to CO 2 emissions, understanding CH 4 emission magnitude and its driving factors in the growing and nongrowing seasons still requires more in situ observations to narrow the uncertainties of the carbon budget.…”
Section: Discussionmentioning
confidence: 99%
“…Wetlands and lakes have differing CH 4 emissions and processes (Kuhn et al., 2021b; Wik et al., 2016), but distinguishing these landforms in observations and remote sensing images can be difficult, leading to possible double counting of emissions sources (Thornton et al., 2016). Hybrid process modeling together with remote sensing and eddy covariance data have been used to estimate wetland CH 4 fluxes relatively accurately (Watts et al., 2023), which incorporates important factors such as soil moisture, temperature, vegetation characteristics, and hydrological dynamics to estimate wetland CH 4 fluxes.…”
Section: Modeling the Carbon Fluxes In The Terrestrial Permafrost Regionmentioning
confidence: 99%